Assessment of Stream Network Pattern in Abak and Essien Udim LGAs of Akwa Ibom State of Nigeria using Remote Sensing and GIS Techniques - Udoudo, N. P.; Ekebuike, A. N.; Igwe, S. C.; Okoli, F.; Silas, J. (Journal of Spatial Information Sciences, 2024)
The focus of this research is on the application of Remote Sensing and Geographic Information System (GIS) techniques to carry out a hydrological analysis in Abak and Essien Udim Local Government Areas (LGAs) of Akwa Ibom State of Nigeria. Most of the hydrological studies in Akwa Ibom are focused on more developed area and not in Abak and Essien Udim LGAs, resulting in building residential and other structures on stream channels, and experiencing the negative environmental consequences yearly. This study examines the hydrological features within this small hydrological unit which contributes her content and precipitation at the long run to a much larger basin (Cross river Basin). Methodologically, the study employed the GIS approach by analyzing the source data downloaded online from remote sensing imageries. The Landuse/Landcover classification result shows 34.11% Built-Up area, 33.65% Farmland., 26.30% Vegetation (Forest Land), 3.50% of Bare Land, and 2.44% of Water Bodies. Also, the stream network is dominated with dendritic pattern having 283 First order streams (where most are seasonal with dry valleys during dry seasons), 128 Second order streams, 61 Third order streams and 4 Fourth order streams in the area. Few smaller drainage units or basins exist in the area which contribute its content to Cross River basin. The study has also made some recommendations to the management authorities to ensure proper sustainable management and use of the hydrological resource within the area to avoid environmental degradation. Houses and other structures also should not be built across the stream channels to avoid blocking the water ways which may result in collapse of the buildings, erosion and environmental degradation.